Behavioral Response of Aedes aegypti Mosquito towards Essential Oils Using Olfactometer - Ashish Uniyal; Sachin N Tikar; Murlidhar J Mendki; Ram Singh; Shakti V Shukla; Om P Agrawal; Vijay Veer; Devanathan Sukumaran (Tehran University of Medical Sciences, 2016)
Background: Aedes aegypti mosquito is responsible for transmitting human diseases like dengue and chikungunya. Personal or space protection with insect repellents is a practical approach to reducing human mosquito contact, thereby minimizing disease transmission. Essential oils are natural volatile substances from plants used as protective measure against blood-sucking mosquitoes. Methods: Twenty-three essential oils were evaluated for their repellent effect against Ae. aegypti female mosquito in laboratory conditions using Y-tube olfactometer.  Results: The essential oils exhibited varying degree of repellency. Litsea oil showed 50.31%, 60.2 %, and 77.26% effective mean repellency at 1 ppm, 10 ppm and 100 ppm respectively, while DEET exhibited 59.63%, 68.63%, 85.48% and DEPA showed 57.97%, 65.43%, and 80.62% repellency at respective above concentrations. Statistical analysis revealed that among the tested essential oils, litsea oil had effective repellency in comparison with DEET and DEPA against Ae. aegypti mosquito at all concentration. Essential oils, DEET and DEPA showed significant repellence against Ae. aegypti (P< 0.05) at all 3 concentration tested. Conclusion: Litsea oil exhibited effective percentage repellency similar to DEET and DEPA. The essential oils are natural plant products that may be useful for developing safer and newer herbal based effective mosquito repellents.